LITERASI MATEMATIKA SISWA MELALUI METODE MURDER (MOOD, UNDERSTAND, RECALL, DIGEST, EXPAND, REVIEW) - Rahmadhani, Elfi; Gradini, Ega; B, Firmansyah (Al-Khawarizmi, 2019)
This paper aims to describe the mathematical literacy skills of students of SMAN 1 Takengon after being given learning using the MURDER method (Mood, Understand, Recall, Digest, Expand, Review). Mathematical literacy skills are seen according to the assessment framework according to PISA, namely 1) Communicating, 2) Mathematising, 3) Representation, 4) Reasoning and Argument, 5) Devising Strategies for Solving Problems, 6) Using Symbolic, Formal and Technical Language and Operation and 7) Using Mathematics Tools. This research is quantitative research involving 70 students of class XII of SMAN 1 Takengon. Based on the results of the analysis and processing of data obtained, namely th = 1.71 and t (1-α), = 1.67. This shows that the research hypothesis is accepted where students' mathematical literacy skills taught using the MURDER method are better than students' mathematical literacy skills taught with conventional learning models. The mathematical literacy skills of students in the experimental class are high with the number of students 20 people with a percentage of 57.14%. While the mathematics literacy skills of the control class students are classified as moderate with the number of students 17 people with a percentage of 48.57%. In the experimental class, there were 8 students or 22.86% in the very high category, superior to the control class, namely 5 students with a percentage of 14.29%.